The Use Of Pineapple Juicce As a Sugar Substitute In Tape Candy Processing On Consumer Acceptance - Qorina El Hariza; Mulyadi, Mochtar Nova (Teknologi Hasil Pertanian, Fakultas Teknik, Universitas Annuqayah, 2024)
Candy tape is a snack produced from cassava ferementation. However, the use of sugar in the manufacture of tape candy can be an important issue considering its negative impact on public health, especially in the context of increasing cases of diseases such as diabetes and obesity, because in the use of sugar in tape candy can be replaced with pineapple juice. The purpose of this study is to determine the consumer acceptability test of tape candy substituted with pineapple juice. The method used in this study uses an organoleptic test with 4 treatments, after obtaining the results of the data, it will be analyzed using One Way Anova. If the results of the ANOVA test show a significant influence or <0.05, the next step is to perform the Duncan test. Based on the results of the ANOVA one-way test on the color of the candy tape, it is known that the significance value (sig) is =0.963> 0.05, then the null hypothesis is accepted. The results of the ANOVA one-way test for the aroma parameter showed a significance value of 0.010.< 0.05, then H0 was rejected so that there was a significant difference, to find out which one there was a difference, then the Duncan test was continued. The results of the ANOVA one-way test for taste showed a significance value of 0.001< 0.05, so H0 was rejected and showed a significant difference. Next, a duncan test is carried out. Based on the analysis of the results of the ANOVA one-way test, the sig value = 0.465 > 0.05, so the null hypothesis (H0) is accepted, which means there is no significant difference. The results of the organoleptic acceptability of candy tape based on the ANOVA one-way test can be stated that in the color and texture parameters Ho is accepted so that there is no real difference, while in the aroma and taste parameters Ho is rejected so that there is a real difference